Economics-politics of group 1%: the dominance of minorities in economic perspective - Yusa, M. Yustian (Opción, 2019)
This paper will describe and seek answers to the question of how minorities have dominance or power over politics-economics, not only in Indonesia but also in the World? For this purpose, we use comparative qualitative research methods. As a result, the phenomenon of the dominance of Jewish and Chinese in the fields of economics and politics cannot be separated by factor as diasporic ethnic. In conclusion, the income inequality between the minority and the majority leads to a negative stigma in the free market, in which the rich get richer and the poor get poorer.